Number theory and the periodicity of matter - Boeyens, Jan C. A. (Springer, 2017)
The theme of this book is to explore the consequences of the serendipi-tous discovery that stable nuclides obey the same periodic law as the chemical elements; both laws are rooted in elementary number theory. The nature of the discovery is such that, from the related periodic structures that occur in the natural numbers, as well as atomic matter, fundamental details about the electronic configuration of atoms and the baryonic arrangement in atomicnuclei can be derived, without the use of higher mathematics. A high degree of self-consistency substantiates the basic thesis from internal evidence, without assumption. This self-consistency includes convergence of nucleon distribu-tion to the golden ratio and a natural limit on the number of elements andnuclides which are stable against radioactive decay. On this basis all observedproperties of atoms and atomic nuclei can be understood as characteristic of a number system defined on a closed interval.